THE INFLUENCE OF ORGANIZATIONAL CULTURE AND LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES IN THE DEPARTMENT OF CULTURE, YOUTH, SPORTS AND TOURISM OF KARO DISTRICT - Hilda (Jurnal Enterprise dan Tata Kelola Perusahaan : Manajemen dan Akuntansi, 2025)
The purpose of this study was to determine the effect of organizational culture and leadership style on employee performance in this type of research is a quantitative study using multiple linear regression methods. The analysis used includes instrumental testing, classical hypothesis testing, and hypothesis testing. The result of this research is the value of Y = -6.784+0.672X1+0.633X2. In a sense, corporate culture has a significant impact on performance. From the t count > t in the table, namely 7,803 > 1,683, with sig 0.000 <0.05, it can be seen that leadership style has a significant effect on performance. 0.000<0.05. Organizational culture and leadership test scores affect performance simultaneously when Fcount > Ftable (62.090 > 4.08) of 0.000 <0.05. Based on the results of testing the coefficient of determinants of organizational culture and leadership style, the adjusted R-square value is 75.8%, meaning that organizational culture and leadership style contribute 75.8% to variations in performance. and other offers 24.2% influenced by other factors not examined in this study.